2019
DOI: 10.1088/1751-8121/ab2490
|View full text |Cite
|
Sign up to set email alerts
|

Extended T-systems, Q matrices and T-Q relations for $ \newcommand{\e}{{\rm e}} s\ell(2)$ models at roots of unity

Abstract: The mutually commuting 1 × n fused single and double-row transfer matrices of the critical six-vertex model are considered at roots of unity q = e iλ with crossing parameter λ = (p ′ −p)π p ′ a rational fraction of π. The 1 × n transfer matrices of the dense loop model analogs, namely the logarithmic minimal models LM(p, p ′ ), are similarly considered. For these sℓ(2) models, we find explicit closure relations for the T -system functional equations and obtain extended sets of bilinear T -system identities. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 109 publications
1
6
0
Order By: Relevance
“…From the factorised expression (6.10) we see that the zeroes of the eigenvalues ofT s (u, φ) are either zeroes ofQ u + 2s+1 2 η, φ or zeroes ofP u − 2s+1 2 η, φ . Specialising s = ( 2 − 1)/2, T ( 2 −1)/2 = T ( 2 −1)/2 and this agrees with Ref [70]…”
supporting
confidence: 89%
See 1 more Smart Citation
“…From the factorised expression (6.10) we see that the zeroes of the eigenvalues ofT s (u, φ) are either zeroes ofQ u + 2s+1 2 η, φ or zeroes ofP u − 2s+1 2 η, φ . Specialising s = ( 2 − 1)/2, T ( 2 −1)/2 = T ( 2 −1)/2 and this agrees with Ref [70]…”
supporting
confidence: 89%
“…Morin-Duchesne and Pearce[70] observed that the zeroes of the eigenvalues of the Q operator appear as part of zeroes of eigenvalues of the transfer matrix whose argument is shifted as T ( 2 −1)/2 (u + 2 η/2, φ) at root of unity. In our framework this is clear too.…”
mentioning
confidence: 99%
“…Rodney Baxter [1] pioneered the use of functional equations to calculate various physically relevant lattice quantities for solvable lattice models. Nowadays, it is well understood that on an extended lattice, the integrability structures are embodied in the fusion hierarchy [53], T-and Y-systems [12,25,[54][55][56][57] and T-Q functional equations [5][6][7][8][9] satisfied by the transfer matrices. The T-system is well suited to the calculation of non-universal lattice quantities such as free energies using the inversion relation method [58,59].…”
Section: Introductionmentioning
confidence: 99%
“…This in turn ensures the existence of a one-parameter family of commuting transfer matrices. Solutions to the Yang-Baxter equations are often labeled by affine Lie algebras [6,7], with the most studied cases corresponding to the low-rank algebras A 1 loop model and the related six-vertex models, it is fair to say that their sℓ (2) integrability structures are now well understood [2,[8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%